La Clase Magica: Imagining Optimal Possibilities in a Bilingual Community of Learners - Vasquez, Olga A. (Lawrence Erlbaum, 2003)
This book vividly captures the social and intellectual developments and the promises of an on-going after-school project called La Clase Magica.The book offers researchers, practitioners and policy makers much-needed guidance, insight and perhaps inspiration for rethinking educational goals and objectives.